The Election behavior of municipal councilors and mayors Maha Sarakham City Municipality Maha Sarakham Province - Ruangkaundee, Prin; Thongchan , Siripong (Journal for Developing the Social and Community, 2022)
The purpose of this research was to collect data on the election behavior of municipal councilors and mayors Maha Sarakham city Municipality, Maha Sarakham province. By collecting data of 400 citizens who had the right to vote in District 1, District 2 and District 3 of Maha Sarakham Municipality, Maha Sarakham Province and using a simple sampling method and a questionnaire as a tool. The statistics used to analyze the data were frequency, mean, standard deviation. The research objectives were as follows: 1.) To study the election behavior of municipal councilors and mayors Maha Sarakham city Municipality, Maha Sarakham province. The result found that most of the citizens who had the right to elect members of the municipal council and mayors were male, aged between 36-45 years, occupation was private company employees, and education levels were High Vocational and bachelor’s degree, and monthly income was between 10,001 - 20,000 baht. And those groups of people have a high level of opinions about election behavior. The averages were sorted from highest to lowest as follows: Political Party Policies, perception of political information, exercise of rights and participation in elections, participation in political activities, the performance of political parties, and the personal qualities of the applicant. 2.) To compare the election behavior of municipal councilors and mayors Maha Sarakham city Municipality, Maha Sarakham province by gender, age, occupation, education level, and monthly income. The result found that voters of different ages and occupations also had a statistically significant difference in overall electoral behavior at the 0.05 level. As for the electoral voters with different gender, educational level and monthly income, their overall opinions were not different. 3) To study the recommendations of the election behavior of municipal councilors and mayors Maha Sarakham city Municipality, Maha Sarakham province. They are arranged in order from greatest to least frequencies as follows: 1.) There should be a policy that considers the interests of the people as a priority. 2.) Do not encourage voice trading. 3.) There should be a clear policy for both short term and long term. 4.) There should be a public hearing for policy making. 5.) Should propose guidelines for development and problem solving of Maha Sarakham City Municipality. 6.) There should be a team that is strong and ready to develop the community. 7.) Should have outstanding performance before applying for election. And 8.) Vision and policies should be displayed online and made easy to understand.